Design of PID Control System for Liquid Surface Height Using Root Locus Method - IskandarAzis (Jurnal Teknik Mesin, 2017)
Control of the liquid surface height at a plant requires a system of control. The design of the control system requires a method of completion for height control system capable of controlling the liquid level remains stable at the desired level, namely the level of 8 and 10. The purpose of this research is to design a control system on a high surface of the liquid with PID control and implement methods of Root Locus. In this study, the liquid surface height of plant to be controlled ie MISO plant with two tanks. Root locus method has been able to control the high liquid level in the tank 1 with PID control parameters Kp = 58.27, Kd = 0.5. While high liquid level in the tank 2, PID control parameters are Kp = 75.7, Kd = 5. High surface of the liquid in the know stabilized by providing high varisi disruption of the liquid surface is high melibihi SP and under high-SP into PID control system.